(untitled) (Shahroud Journal of Medical Sciences, 2020)
Background: Obesity is one of the most common problems between women, which leads to many chronic diseases such as heart disease and cancer. Various factors, including emotional problems and lifestyle, play a special role in the obesity of women. The purpose of the present study was to investigate the effectiveness of Emotion-Focused Therapy Group (EFT-G) on the difficulties in emotion regulation and the health-promoting lifestyle of obese women referred to nutrition clinics in Mashhad in 2018. Methods: In this study, twenty-four obese volunteer women were selected and assigned to two experimental (n =12) and control (n =12) groups. One meeting was held to explain the aims of the research and intervention. The experimental group received 90-minute weekly sessions for 2.5 months (10 sessions), while the control group did not receive any intervention. Before and after the training phase, all of the participants completed the demographic questionnaire. Finally, they had also completed the Difficulties in Emotion Regulation Scale and the Health-Promoting Lifestyle Profile. Data were analyzed by using SPSS 22 software. Results: The outcomes of data analysis by using one-way and multivariate covariance analysis indicated that the EFT-G significantly reduced the overall score of difficulties of emotion regulation in obese women (Pvalue≤0.001).These outcomes also represented that the health Promotion lifestyle of mentioned women had significant improvement (Pvalue≤0.001). Conclusions: Generally, the results showed that the EFT-G leads to a decrease in the scores of difficulties in emotion regulation and an increase in the scores of health promotion lifestyle is relevant to obese women. Furthermore, this study illustrated that EFT-G can improve the difficulties in emotion regulation and the health promotion lifestyle of obese women. Keywords: Emotion-Focused Therapy Group, Obesity, Difficulties in Emotion Regulation, Health Promotion Lifestyle.